Analytical treatment of system of linear and nonlinear PDEs by Homotopy-Perturbation method - Chowdhury, Md. Sazzad Hossien; Hashim, Ishak; Ismail, Ahmad Faris (2010)
In this paper, the homotopy-perturbation method (HPM) is employed to obtain approximate analytical solution to the linear and nonlinear systems of partial di®erential equations (PDEs). HPM yields solutions in convergent series forms with easily computable terms. Generally, the closed form of the exact solution or its expansion is obtained without any noise terms. Test examples demonstrate the e±ciency of HPM.